TANGGUNG JAWAB HUKUM PELAKU USAHA ATAS PRODUK CACAT TERSEMBUNYI - Setiawan, Jetmiko; Yetti; Afrita, Indra (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
Business actors, as parties with stronger bargaining positions, ethically have the obligation to ensure that the products they manufacture and distribute are safe for use. Moral responsibility should drive business actors to actively ensure product quality and refrain from concealing defects or hidden faults that may harm consumers. Therefore, it is important to examine how the Consumer Protection Law regulates the legal responsibilities of business actors for hidden defective products, and how moral responsibility can strengthen their commitment to upholding consumer rights. This study employs normative legal research methods. Based on the findings, the legal responsibility of business actors for hidden defective products, as governed by Law No. 8 of 1999 on Consumer Protection, serves as a concrete form of consumer rights protection. A hidden defective product is one that appears normal at the time of purchase but contains a defect that is not immediately visible and only causes damage or harm after use. The Consumer Protection Law requires business actors to be fully responsible for the products they produce or trade, including their quality, safety, and the accuracy of the information provided to consumers. Article 19 of Law No. 8 of 1999 stipulates that business actors must provide compensation for damages caused by defective products, including physical harm, contamination, or financial losses. This form of liability is strict, meaning that even if the business actor was unaware of the defect, they are still held accountable for introducing a defective product into the market. This obligation reflects the principle of due diligence in business and reinforces protection for consumers, who are generally in a weaker position in legal and commercial relationships. The legal consequences faced by business actors who neglect or evade this responsibility are also regulated by the Consumer Protection Law.